Bladder Cancer: Depression, Anxiety, and Suicidality Among the Highest-risk Oncology Patients - Vartolomei, Liliana; Vartolomei, Mihai Dorin; Shariat, Shahrokh F (European urology focus, 2020)
There is a growing interest among clinicians regarding quality of life and psychological well-being of patients with bladder cancer. Recent evidence suggests that some patients might be at risk of suicide, and suffer from pre- and post-treatment depression and anxiety. In future, we should focus on attempting to identify patients who might be affected and might need specialized interventions. Furthermore, it is of utmost importance to investigate which type of interventions might be useful to help these patients achieve the goal of alleviating their cancer-related suffering. PATIENT SUMMARY: In this review, we looked at the data available regarding the rates of depression, anxiety, and suicide among the highest-risk oncology patients with bladder cancer. There is increased evidence that a high percentage of patients are at risk of suffering from psychological distress, with a proportion even committing suicide. Management of these patients should include a clear guideline on how to identify patients at risk and to combat possible psychological effects of this debilitating malignancy.
Keywords: Depression; Risk Assessment; Urinary Bladder Neoplasms; Suicide; hodnocení rizik; deprese; Humans; úzkost; sebevražda; nádory močového měchýře; Anxiety; Bladder cancer; lidé